The Logit Model and the Need to Reproduce the Stiffness Degradation Curve of Asphalt Specimens During Fatigue Testing. Issue 1 (2017) - Mateos, Angel; Wu, Rongzong; Harvey, John; Denneman, Erik; Fan, Angela
Asphalt fatigue cracking is widely recognized as one of the most important pavement distresses, which is typically evaluated in the laboratory by conducting repeated load fatigue tests. There is no simple model that can fully reproduce the evolution of the stiffness of asphalt specimens during fatigue testing. This reality limits analysis and interpretation of asphalt fatigue data and the implementation of test results in mechanistic–empirical modeling. Two simple models, based on the logit function, are presented in this paper. These models, called logit and logit-sigmoidal, were found to reproduce almost exactly the evolution of specimen stiffness during flexural fatigue testing. This capability was used to locate critical points of the stiffness degradation curve, including failure points according to complex failure criteria. The mechanical meaning of the parameters of the logit model is analyzed in this paper. One of the parameters was related to the ability of the asphalt mix to sustain damage before crack initiation. Another parameter was related to the presence of reversible phenomena—heating and thixotropy—in the first part of the stiffness degradation curve. The applicability of the logit model to mechanistic–empirical pavement design is also evaluated in this paper on the basis of implementation in the CalME mechanistic–empirical software.